Examining the determinants of Gen Z’s intention to use AR in Malaysia’s tourism industry - Teh, Yi Ming; Kua, Siau Wen (2024)
AR technology offers new tourism improvements as it develops. This research seeks to help tourism stakeholders engage Gen Z by knowing what motivates them to use AR. Surveys and data analysis evaluate and identify key determinants including perceived usefulness, perceived ease of use, attitude, and perceived enjoyment. The findings aim to help tourism experts and developers produce better AR experiences, boosting Malaysia's tourism attractiveness. The findings should help create friendly for Generation Z AR solutions. This study evaluated factors influencing Gen Z's intention to use AR in Malaysia's tourist industry. The Technology Acceptance Model (TAM) will be used to determine the intention of using AR in the tourism industry, including Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude (ATT), Perceived Enjoyment (PE), and Intention to Use AR (IU). This study collects data from 397 respondents via a questionnaire. SPSS is used to analyze the data. To show the independent variable and dependent variable's relationship, this study carried out a reliability test, Pearson's correlation coefficient analysis, and multiple regression analysis. The data show that all hypotheses significantly influenced Malaysia's tourism industry's AR usage. Researchers can learn from this study on the variables that affect Generation Z's intention to use AR in Malaysia's tourist industry. With that, top managers may take actions to promote AR adoption and attractiveness. Keywords: TAM Model, Perceived Usefulness, Perceived Ease of Use, Attitude, Perceived Enjoyment, Intention to Use AR, Gen Z, Tourism Industry, Augmented Reality( AR).